Shaking table test on seismic performance of integrated station-bridge high-speed railway station. (December 2022) - Zhao, Yushuai; Zhang, Yingying; Xu, Junhao; Yu, Penghao; Sun, Baorui
Abstract: The structure of integrated station-bridge is commonly used in the construction of high-speed railway station, which mainly consists of the frame part and the grid part. The complicated structure is characterized by the discontinuous vertical stiffness and the large longitudinal span, which results in an undefined mechanism of structural dynamic catastrophe. In this paper, the shaking table test was carried out with the model scale ratio of 1/25 to study the seismic performance, including the failure mode, acceleration, displacement and internal force responses, etc. The results show that the buckling of the frame occurs under the PGA of 0.82 g, which mainly concentrates on the third floor. The beam end of the top joint buckles obviously under the PGA of 1.27 g. The members of grid begin to yield under the PGA of 0.40 g, in which the order of yield member was web and chord in the truss. Based on the results of experiments, a seismic performance evaluation method of the composite structure is proposed for the damage of the grid frame and frame under different seismic intensities.